KAJIAN EKSPERIMENTAL PENANGGULANGAN EROSI MENGGUNAKAN SHIPONI BELL - Muhlisa Amalia Ilyas; Ratna Musa; Ali Mallombasi (Journal of Scientech Research and Development, 2023)
Terracing is one form of erosion prevention that is most often carried out, namely by making terrace after terrace like stairs on sloping land so that when it rains the water does not just wash away so that the chances of soil erosion can be minimized. This problem requires a method that can prevent the possibility of surface water runoff past the terrace bund crests and can deposit sediment resulting from erosion on the terraces. The aim is to determine the relationship between rainfall duration and erosion and to determine the effect of risel height on the volume of erosion overtopping. This research will be carried out in the Makassar Muslim University laboratory, Faculty of Engineering, with an estimated research time of 6 months. From the results, the role of risel height has little effect on the sediment catchment. This is not in line with theory because the higher the rise, the longer it takes for the release of pressure to occur in the risel. If the duration of rain is longer, the sediment transport will increase.